SYNERGISTIC SELF-ACTUALIZATION AND LIVED RELATIONS TO GOD IN RESEARCH OF HIGH SCHOOL GRADUATES - LISZEWSKI, TOMASZ (Studia Psychologica: Theoria et praxis, 2016)
The purpose of this article was to examine associations between the lived relations to God and the types of shaping own life by the interpersonal relations. 172 high school graduates (88 women and 84 men) form various types of high school took part in current research. The assessment included The Styles of Self-actualization Questionnaire by Uchnast and Hutsebaut’s Relation to God Scale. The results demonstrated that the different styles of self-actualizations associated with individual lived relations to God. The relations to God classed as mature link positive with personal or synergistic styles of self-actualization and negative with the apersonal styles, which were the opposite results as in case of the immature religious relation.